Optical gain analysis of GaInP/AlGaInP nanoscale heterostructure for applications in visible light emission. (2022) - Vijay, Jayprakash; Singh, Kulwant; Singh, A.K.; Rathi, Amit
Abstract: In quantum well structures, charge carriers are confined in the well region and barrier region due to the discontinuity in the bandgap and larger built-in potential. Thus, for a smaller current, we can have a higher gain. This work reports the energy wavefunction and optical gain analysis of the GaAs-based quantum well structure made of GaInP/AlGaInP material layers. The structure is also examinedsubject to the effect of external pressure and temperature to study the tunability. The designed structure shows stability near the room temperature. The 6 × 6 Hamiltonian matrix is solved and the Luttinger-Kohn model with the conduction band is used for the calculation of band structure. In the quantum well structure, the thickness of the active layers is in our control. This is an important advantage for device fabrication. The material and the size of the layers are selected on the basis of their suitability to generate the radiation in the range of the red spectrum (620-–750 nm).The designed QW heterostructure is thus found to be suitable for photodynamic treatment (PDT) and dermatological treatments.